Assessment of gingival crevicular fluid levels of gamma glutamyl transferase in chronic periodontitis patients before and after non-surgical periodontal therapy: A clinico-biochemical study - Kavyashree G; Shrinidhi Maji Shankar; Umesh Nagesh; Soumya Bardvalli Gururaj; Chethana Kunthur Chidambar; Kala Bhushan (Elsevier, 2022)
Objectives: Gamma-glutamyl transferase (GGT) enzyme is a routinely used diagnostic marker to detect various systemic diseases, elevation of which indicates destructive activity. Elevated GGT levels in GCF of destructive periodontal diseases hence can be expected. Hence, the aim of this study was to investigate if gamma glutamyl transferase would be a good indicator of on-going disease activity and to also assess the effect of non-surgical therapy on Gamma glutamyl transferase in gingival crevicular fluid of clinically healthy and chronic periodontitis patients. Methods: GCF samples from 20 chronic periodontitis patients and 20 clinically healthy individuals of age group 35-45 years were collected. Clinical parameters were recorded and GGT levels in GCF assessed using semi-autoanalyser before and after appropriate non-surgical periodontal therapy in both the groups. Results: GGT levels were higher in chronic periodontitis group compared to healthy group at baseline. There was a significant reduction in the GGT levels and clinical parameters at 30th and 90th day post treatment. Conclusion: The significant reduction in the GGT levels after Non Surgical Periodontal Therapy at every recall interval may indicate that GGT can be used as a potential diagnostic marker of periodontitis.